2015
DOI: 10.1039/c5ra09462c
|View full text |Cite
|
Sign up to set email alerts
|

Pulse electrodeposition and corrosion behavior of Ni–W/MWCNT nanocomposite coatings

Abstract: In this study, Ni-W/multiwalled carbon nanotubes (MWCNTs) composite coatings were successfully deposited on the surface of C45 steel sheet by pulse current electrodeposition. Particularly, a uniform dispersion of MWCNTs in the plating electrolyte bath is indispensable. To achieve this main point, MWCNTs were modified by acidification, and coupled with introduction of sodium dodecyl sulfate to the plating bath. Scanning electron microscopy (SEM) and X-ray diffraction (XRD) were employed to characterize the mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(12 citation statements)
references
References 46 publications
1
11
0
Order By: Relevance
“…For objects subjected to a wear environment, two important properties of wear resistance and hardness are essential. Figure 14 described in the previous researches [15,[44][45][46]. One possible reason for this result is that the SiC nanoparticles in the Ni-W-SiC coating blocked the dislocation movement and sliding at the grain boundary of the matrix, thereby increasing the micro-hardness of the Ni-W-SiC.…”
Section: Microhardnessmentioning
confidence: 76%
“…For objects subjected to a wear environment, two important properties of wear resistance and hardness are essential. Figure 14 described in the previous researches [15,[44][45][46]. One possible reason for this result is that the SiC nanoparticles in the Ni-W-SiC coating blocked the dislocation movement and sliding at the grain boundary of the matrix, thereby increasing the micro-hardness of the Ni-W-SiC.…”
Section: Microhardnessmentioning
confidence: 76%
“…Nevertheless, the research found that Ni dissolved easily from the alloy due to galvanic action [38], while Ni-W-Si 3 N 4 coatings were found to be dense and smooth. Therefore, it is obvious that Si 3 N 4 blocked the dissolution of Ni and the diffusion of corrosive media through adsorbing on the anodic sites, leading to formed a more homogenous and compact coating [12]. Moreover, pulse current electrodeposited coating have better corrosion resistance compared to direct current electrodeposits.…”
Section: Electrochemical Impedance Study (Eis)mentioning
confidence: 99%
“…However, with the growth of hardness and wear resistance, Ni-W coating also increases undesired residual tensile stress. It is a potential strategy that incorporation of particles into Ni-W matrix deposit to reduce residual tensile stress and further improve hardness as well [12]. Also, the co-electrodeposition process could be useful in the improvement of other properties of alloy coating, such as oxidation resistances, corrosion resistances and wear resistances [15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It can improve the mechanical as well as thermal and electrical properties. Several researchers have successfully developed Cu-MWCNTs [23,24], Co-MWCNT [25], Co-W-MWCNT [26], Ni-W-MWCNTs [27] and graphine-copper [28] nanocomposites coatings using the electrodeposition process. Ramalingam et al [29] developed Cu-MWCNTs nanocomposite coatings by the electrodeposition technique from optimised bath composition and using optimised process conditions.…”
Section: Introductionmentioning
confidence: 99%